Housing well-being and sleep in Australia - Edmed, Shannon L; Huda, M Mamun; Alam, Md Ashraful; Pattinson, Cassandra L; Rossa, Kalina R; Shekari Soleimanloo, Shamsi; Smith, Simon S (My University, 2025)
The built and social aspects of housing influence a broad range of health and social outcomes and may be important enablers of barriers to occupants accessing sufficient and good-quality sleep. The aim of this study was to examine the relationships between housing well-being (a conceptualization of housing-related [dis]advantage), with self-reported sleep outcomes in Australians. We conducted a cross-sectional analysis of Wave 21 (2021) of the Household, Income and Labour Dynamics in Australia (HILDA) Survey, a longitudinal, population-based study of Australian households. Multilevel logistic regression models were used to examine the association between "housing well-being" and sleep outcomes. The sample analyzed consisted of 13,516 respondents. Greater housing insecurity (a composite score comprising tenure type, housing affordability stress, and housing mobility) was associated with higher odds of insufficient sleep (AOR: 1.28; 95% CI: 1.15, 1.41) and sleep disturbance (AOR: 1.13; 95% CI: 1.04, 1.22) after adjustment. Unsuitable housing (a composite score comprising dwelling type, occupant density, and housing quality) was associated with increased odds of insufficient sleep (AOR: 1.36; 95% CI: 1.19, 1.55), napping (AOR: 1.13; 95% CI: 1.02, 1.25), and sleep disturbance (AOR: 1.14; 95% CI: 1.03, 1.26) after adjustment. Improving housing condition and circumstances may support the sleep health of Australians. Future research should explore the ways in which sleep may play a mediating role through which built environments affect other health and well-being outcomes.
Sleep Health
Keywords: Environmental factors; Housing insecurity; Housing quality; Residential instability; Sleep disturbances; Sleep duration; Disadvantage, adversity and resilience; Health and wellbeing; Housing, communities and neighbourhoods